Segments-aware universal adversarial perturbations purification on 3D point cloud classifiers - Gao, Yang; Chang, Xianrui; Li, Haoran; Xu, Jian (Frontiers in Computer Science, 2025)
Introduction3D point cloud classifiers, while powerful for representing real-world objects and environments, are vulnerable to adversarial perturbations, particularly Universal Adversarial Perturbations (UAPs). These UAPs pose significant security threats due to their input-agnostic nature. Current purification methods exhibit critical limitations: they typically operate independently of the target classifier and treat perturbations as isolated points without considering the coherent, structural nature of UAPs in 3D point clouds (such as outlier-like shapes with continuous curvature). This fundamental oversight limits their effectiveness, primarily because distinguishing between genuine geometric features and structured adversarial patterns presents a significant challenge.MethodsWe propose a novel purification framework that leverages model interpretability to identify and remove adversarial regions in a holistic manner. Our approach uniquely identifies influential regions within adversarial samples that maximally impact the classifier's predictions. Recognizing that UAPs often manifest as structured segments rather than random points, we employ graph wavelet transforms to isolate suspicious curvature segments. These identified segments undergo a transplantation test where they are transferred to clean samples; segments are classified as adversarial if this transfer consistently induces misclassification. The identified adversarial regions are then removed to sanitize the point cloud. This model-guided, structure-aware approach treats UAPs as coherent structures rather than isolated perturbations.ResultsWe conducted extensive experiments on two public 3D point cloud datasets using four different state-of-the-art classifiers. Our framework demonstrated remarkable improvements in robustness against various UAP attacks compared to existing purification methods. The results show significant accuracy recovery rates after purification, with consistent performance across different classifier architectures and attack methods. Our method particularly excels at preserving genuine geometric features while removing adversarial structures, maintaining high classification accuracy on clean samples while effectively neutralizing UAP threats.DiscussionOur findings demonstrate that considering the structural nature of UAPs and leveraging model interpretability are crucial for effective defense. Unlike previous point-wise approaches, our framework's ability to identify and process coherent adversarial segments addresses the fundamental limitation in current purification methods. The transplantation test provides a reliable mechanism to distinguish between legitimate features and adversarial artifacts. This work highlights the importance of model-guided purification strategies and opens new directions for defending geometric deep learning systems against structured adversarial attacks. Future work could extend this approach to other geometric data representations and explore adaptive defense mechanisms against evolving attack strategies.